2018
DOI: 10.1002/adem.201700946
|View full text |Cite
|
Sign up to set email alerts
|

High Entropy Alloys: Prospective Materials for Tribo‐Corrosion Applications

Abstract: Tribo-corrosion is an issue of concern for marine and other fluid machinery. High entropy alloys (HEAs) represent a new category of materials possessing exceptional properties. We investigated the erosion-corrosion behavior of Al 0.1 CoCrFeNi HEA. For comparison, stainless steel SS316L is also evaluated. Results indicate that despite low hardness and yield strength, HEA exhibits high erosion-corrosion resistance compared to steel. The HEA also shows high pitting and passive potentials compared to steel. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“… General plots of HV against a,c) tensile yield strength and b,d) ultimate tensile strength of single‐phase FCC HEAs including Al 0.1 CoCrFeNi, [ 74–79 ] Al 0.25 CoCrFeNi, [ 28 ] Al 0.3 CoCrFeMnNi, [ 80 ] Al 0.3 CoCrFeNi, [ 81–84 ] CoCrFeMnNi, [ 35–48 ] (CoCrFeMnNi) x Al 100– x , [ 47 ] Co 20 Cr 26 Fe 20 Mn 20 Ni 14 , [ 45 ] CoCrFeNi, [ 45,48,53–58 ] CoCrNi, [ 49–52 ] Co 26 Cr 18.5 Fe 18.5 Mn 18.5 Ni 18.5 , [ 45 ] CoCuFeMnNi, [ 85,86 ] CoCuFeNi, [ 87 ] CoFeMnNi, [ 85 ] FeCoCrNi, [ 45,58 ] FeMnNi, [ 85 ] and 316 stainless steels. [ 59–66 ] The referenced three‐time line is included in each image.…”
Section: Resultsmentioning
confidence: 99%
“… General plots of HV against a,c) tensile yield strength and b,d) ultimate tensile strength of single‐phase FCC HEAs including Al 0.1 CoCrFeNi, [ 74–79 ] Al 0.25 CoCrFeNi, [ 28 ] Al 0.3 CoCrFeMnNi, [ 80 ] Al 0.3 CoCrFeNi, [ 81–84 ] CoCrFeMnNi, [ 35–48 ] (CoCrFeMnNi) x Al 100– x , [ 47 ] Co 20 Cr 26 Fe 20 Mn 20 Ni 14 , [ 45 ] CoCrFeNi, [ 45,48,53–58 ] CoCrNi, [ 49–52 ] Co 26 Cr 18.5 Fe 18.5 Mn 18.5 Ni 18.5 , [ 45 ] CoCuFeMnNi, [ 85,86 ] CoCuFeNi, [ 87 ] CoFeMnNi, [ 85 ] FeCoCrNi, [ 45,58 ] FeMnNi, [ 85 ] and 316 stainless steels. [ 59–66 ] The referenced three‐time line is included in each image.…”
Section: Resultsmentioning
confidence: 99%
“…Orthopaedic implants are typically based on three material classes namely, metals, ceramics and polyethylene. Tribo‐corrosion predominantly affects the surfaces of metals, and ceramics to a lesser extent (Nair, Arora, Ayyagari, Mukherjee, & Grewal, 2018). Over the past century, some of the most common biomaterials implanted are metals such as stainless steel, titanium and its alloys (Ti6Al4V, TiNbZrTa) (Long & Rack, 1998), cobalt and its alloys (CoCrMo, CoNiCrMo) (Disegi, Kennedy, & Pilliar, 1999; Gurappa, 2002) and ceramics such as alumina (Al 2 O 3 ) (Kluess, Bergschmidt, Mittelmeier, & Bader, 2014), zirconia (ZrO 2 ) (Piconi & Maccauro, 1999) and silicon carbide (SiC) (Kailer et al., 2011).…”
Section: Electrochemical Measurements Sensors and Degradation Mechanmentioning
confidence: 99%
“…The slurry erosion resistance of CCA Al0.1CoCrFeNi was found [17] to be superior to that of mild steel but lower than UNS S31603 stainless steel but these comparisons relate mainly to mechanical damage as the test programme was carried out in a tapwater slurry. A detailed comparison [18], of the corrosion and erosion-corrosion behaviour of a Al0.1CoCrFeNi CCA alloy and conventional UNS S31603 stainless steel in a 3.5% NaCl slurry, revealed that the material loss of the CCA alloy was slightly greater than that of the stainless steel at an impingement angle of 90° but much less at 30° impact -mainly on account of a considerable increase in material loss of the stainless steel at the oblique angle.…”
Section: Introductionmentioning
confidence: 98%
“…Although the work described in this paper [18] covered an interesting range of aspects, the paper suffers somewhat in a number of respects such as corrosion monitoring exercises not including in-situ measurements, failure to separate synergy into its two erosive and corrosive components and a misinterpretation of the role of the squeeze film in erosion-corrosion systems.…”
Section: Introductionmentioning
confidence: 99%